Synthesis and Evaluation of N-[1-(((3,4-Diphenylthiazol-2(3H)-ylidene)amino)methyl)cyclopentyl]acetamide Derivatives for the Treatment of Diseases Belonging to MAOs - Gülhan Turan-Zitouni; Aouatef Tabbi; Weiam Hussein; Abdullah Burak Karaduman; Begüm Nurpelin Sağlık; Yusuf Özkay (Journal of Chemistry)
A series of N-[1-(((3,4-diphenylthiazol-2(3H)-ylidene)amino)methyl)cyclopentyl]acetamide derivatives (4a-4i) were synthesized in good yield and assayed for their inhibitory potency against monoamine oxidase (MAO) isoforms. Structures of newly synthesized compounds were characterized by IR, 1H-NMR, 13C-NMR, and mass spectroscopic methods. The inhibitory activity of compounds (4a-4i) against hMAO-A and hMAO-B enzymes was elucidated by using in vitro fluorometric method using Amplex Red® reagent. In the hMAO-A inhibition assay, compounds 4a, 4b, 4c, and 4i exhibited similar activity with standard drug moclobemide (IC50 = 6.061 ± 0.262 µM) with IC50 values of 7.06 ± 0.18 µM, 6.56 ± 0.20 µM, 6.78 ± 0.15 µM, and 7.09 ± 0.17 µM, respectively. According to hMAO-B inhibition results, compounds 4a, 4b, and 4c displayed significant activity with IC50 values of 0.42 ± 0.012 µM, 0.36 ± 0.014 µM, and 0.69 ± 0.020 µM, respectively. In the wake of all these results, it was understood that compound 4b was found to be the most potent derivative in the series against both isoforms and selective as MAO-B inhibitor. The cytotoxicity test was performed for compounds 4a, 4b, and 4c, and it was found that these compounds were noncytotoxic at the concentration of their IC50 values. Also, enzyme kinetic and docking studies of compound 4b were performed against MAO-B. It was observed that 4b showed a reversible and noncompetitive inhibition type. The important binding modes of this compound with active site of hMAO-B were shown owing to in silico studies.